(untitled) (Fiep Bulletin - online, 2014)
Education reform was introduced in Poland in 2009. Its aim is to improve the quality of school education by adapting the learning and upbringing process to the individual abilities and needs of pupils and their educational aspirations. An essential element of the reform is introducing the new core curriculum, which is a key document defining the aims and content of teaching, skills of pupils and educational role of the school. It describes the learning effects after the every stage of education and contains proposals for physical activity to be chosen by pupils. The aim of the study was to identify the opinions of physical education teachers working in working in post-secondary schools about the usefulness and practicability of a new core curriculum. Lifetime sports section rated highest of the six sections on the content of teaching; this activity is related to the preparation of pupils for lifelong sports activity. Teachers rated the lowest section of health education. The analysis showed statistically significant differences between usefulness and practicability of this section – usefulness was rated significantly higher than practicability. There were no relevant differences in opinions of surveyed women and men, which shows similar assessment of teaching content by men and women.